1998
DOI: 10.1063/1.1148690
|View full text |Cite
|
Sign up to set email alerts
|

Automated fluid mixing in glass capillaries

Abstract: A fast method and compact device for mixing sub-microliter fluid samples contained in glass capillaries is presented. The fluid is rapidly moved back and forth by air volume displacement driven by a piezo-ceramic actuator. Rapid mixing of different fluids is achieved via diffusion between the main fluid volume in the capillary and the thin fluid film it deposits on the capillary wall through its motion. Bubbles in the fluid are processed out of the capillary by use of an asymmetric velocity profile. A simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…One way to achieve this linking is to mix a DNA solution with DNA probes and examine their reaction. Mixing in conventional laboratories is usually performed by either manually shaking, tapping the test tube followed by centrifuging, or mixing using a stirrer (Evensen et al, 1998). However, these conventional mixing methods are difficult, if not impossible, to implement in miniaturized systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to achieve this linking is to mix a DNA solution with DNA probes and examine their reaction. Mixing in conventional laboratories is usually performed by either manually shaking, tapping the test tube followed by centrifuging, or mixing using a stirrer (Evensen et al, 1998). However, these conventional mixing methods are difficult, if not impossible, to implement in miniaturized systems.…”
Section: Introductionmentioning
confidence: 99%
“…Miyake et al (1993) designed a double-layered micro mixer, in which 400-micron-diameter nozzles were fabricated to provide micro-plumes, which could increase the surface contact area for faster mixing. Evensen et al (1998) designed a mixer driven by a piezo-ceramic actuator such that fluids, e.g., λ-DNA, were perturbed periodically in a glass capillary. They reported no apparent shear breakage of the DNA after mixing by testing with agarose gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…4 To develop electromagnetophoretic applications more extensively to various microscale systems, it will be crucially important to investigate in detail the phenomena of the electromagnetophoretic convection of the medium. Any study of the convection of a liquid in micro-systems will have a more important meaning as a novel technique of micro-mixing, since it has been widely studied as a bottle-neck technique in μTAS, 11 lab-on-a-chip, 12,13 capillary systems, [14][15][16] and many microchannel methods. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Some reviews have also been reported concerning effective mixing in microchannels 34,35 and in small-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing of reagents can take from 3 to 15 seconds depending on the volumes and viscosities of the fluids being mixed [7]. Thus, in the ACAPELLA-5K system, mixing has been parallelized; mixing can occur while a capillary is held in an aspirator/mixer chuck and moved through three stations or up to 17.28 seconds (see Figure 3).…”
Section: A Acapella-5k Core Processormentioning
confidence: 99%
“…The fluid is aspirated or moved back and forth by air volume displacement driven by the piezoelectric actuator. (see [7] for a model of a version of this device).…”
Section: A Acapella-5k Core Processormentioning
confidence: 99%